Risk factors associated with cesarean section and adverse fetal outcomes in intrahepatic cholestasis of pregnancy - Chengcai Kong; Zonghao Zhu; Fenglin Mei (Frontiers Media S.A., 2023)
BackgroundTo determine the risk factors for cesarean section (CS) and adverse fetal outcomes (AFOs) in patients with intrahepatic cholestasis of pregnancy (ICP) based on the severity of maternal hypercholanemia.MethodsA hospital-based retrospective cohort study was performed between January 1, 2015, and December 31, 2019. A total of 227 nulliparous women with a singleton fetus complicated by ICP were included. The patients were divided into two groups according to the levels of total bile acids, that is, mild (10 μmol/L < total bile acids < 40 μmol/L) and severe (≥40 μmol/L). The patients' clinical characteristics and fetal outcomes were assessed.ResultsAmong the 227 eligible women, 177 (78.0%) were allocated to the mild group and 50 (22.0%) were in the severe group. Women with severe ICP also had a significantly higher incidence of planned and unplanned CS compared with mild ICP subjects (52.0% vs. 23.7% and 22.0% vs. 6.8%, respectively; p < 0.001). The indications for CS showed that fetal intolerance (65.4% vs. 14.3%) was higher in severe ICP compared with mild ICP (p < 0.001). Severe ICP was associated with an increased risk of preterm delivery (p < 0.001), low birthweight (p = 0.001), and neonatal intensive care unit (NICU) admission (p < 0.001). Women with severe ICP (OR 6.397, 95%CI 3.041-13.455, p < 0.001) or preeclampsia (OR 12.434, 95%CI 5.166-29.928, p < 0.001) had increased risks of AFOs compared to controls.ConclusionsSevere ICP and preeclampsia are associated with a higher incidence of AFOs.